The Long Noncoding RNA LOXL1-AS1 Promotes the Proliferation, Migration, and Invasion in Hepatocellular Carcinoma - Jiang Liu; Chengtong Zhai; Degan Liu; Jianhua Liu (Analytical Cellular Pathology)
Objective. To investigate the expression of long noncoding RNA lysyl oxidase-like 1-antisense 1 (LOXL1-AS1) in hepatocellular carcinoma tissues and its effect on cell proliferation, migration, and invasion. Methods. Quantitative real-time PCR was used to analyze the expression of LOXL1-AS1 RNA in tumor tissues, adjacent normal tissues, and cell lines. MTT assay, colony formation assay, flow cytometry analysis, transwell assays, and lentivirus-mediated RNA interference (RNAi) technology were used to evaluate cell proliferation and migration. Results. In the present study, we observed that the expression level of LOXL1-AS1 in hepatocellular carcinoma tissue was significantly higher than that in adjacent nontumor tissues, and its expression in three hepatic carcinoma cell lines was obviously higher than that in a normal cell line. In addition, in the Hep-G2 cell line, LOXL1-AS1 downregulation significantly inhibited cell proliferation in the light of the MTT and colony formation assays in vitro, which was consistent with animal experiment in vivo. What is more, cell migration was also inhibited in vitro in Matrigel Transwell Assay by LOXL1-AS1 knockdown, which might be partly attributed to the reduction of MMP-2 and MMP-9 protein expressions. Finally, cell cycle analysis revealed that knockdown of LOXL1-AS1 induced significantly a G0/G1 phase cell cycle arrest, which might be partly attributed to the downregulation of Cdc2, Cdc25A, and cyclin B1 protein expression. Conclusion. In conclusion, we demonstrated that reduced LOXL1-AS1 expression could inhibit hepatocellular carcinoma cell proliferation, migration, and invasion. The application of RNAi targeting LOXL1-AS1 might be a potential treatment strategy in advanced cases.